IMPLEMENTASI MODEL PEMBELAJARAN QUANTUM LEARNING DENGAN MENGGUNAKAN METODE MIND MAPPING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR PESERTA DIDIK - -, Indah Kharisma Sulistyorini -; -, Soetarno Joyoatmojo -; -, Dewi Kusuma Wardani - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
The purpose of this study is to increase the critical thinking skills and learning outcomes of students through the implementation of the Quantum Learning model using Mind Mapping method in the subjects of Introduction to Economics and Business of XI Grade Marketing Expertise Program 1 Vocational High School Batik 2 Surakarta. This research is a Class Action Research (CAR) which practiced into two cycles, and each cycle consisted of planning, implementation, observation, and reflection. The subjects were twenty-six students of XI grade Marketing 1 in Vocational High school Batik 2 Surakarta. The method of data collection used in-dept interview, observation, document analysis, questionnaire, and learning outcome test while data analysis used comparative descriptive technique and critical analysis technique.The results showed that the implementation of Quantum Learning model could signifanctly grow up the critical thinking skills and learning outcomes of Introduction to Economics and Business of XI Grade Marketing Expertise Program 1 in Vocational High School Batik 2 Surakarta. The percentage of student critical thinking skills was increasing 59.72% in pre cycle, 70.51% in the first cycle, and 78.85% in the second cycle. The percentage of student completeness raised 34.62% in pre cycle, 61.54% in the first cycle, and 80.77% in the second cycle. In addition, the average value also increased up to 67.85 in pre cycle, 73.38 in the first cycle and 80.46 in the second cycle. Based on the results, Quantum Learning model with Mind Mapping method could improve critical thinking skills and learning outcomes on Introduction to Economics and Business of XI Grade Marketing 1 in Vocational High School Batik 2 Surakarta.